Microsatellite high-resolution melting (SSR-HRM) analysis for genotyping and molecular characterization of an Olea europaea germplasm collection. Issue 3 (December 2014) - Xanthopoulou, Aliki; Ganopoulos, Ioannis; Koubouris, Georgios; Tsaftaris, Athanasios; Sergendani, Chrysa; Kalivas, Apostolos; Madesis, Panagiotis
<x content-type="archive" xml:space="preserve">Abstract</x> Olea europaea L. has been cultivated in the Mediterranean region for thousands of years and is of major economic importance. The origin of olive cultivars remains as complex to trace as their identification. Thus, their molecular characterization and discrimination will enable olive germplasm management. In addition, it would be a useful tool for authentication of olive products. High-resolution melting (HRM) analysis, coupled with five microsatellite markers, was integrated to facilitate molecular identification and characterization of main O. europaea cultivars collected from the National Olive Tree Germplasm Collection established in Chania, Greece. The five microsatellite loci used were highly informative and generated a unique melting curve profile for each of the 47 cultivars and for each microsatellite tested. In particular, three microsatellite markers (DCA03, DCA09 and DCA17), which generated 29 HRM profiles, were sufficient to genotype all the olive cultivars studied, highlighting their potential use for cultivar identification. Furthermore, this assay provided a flexible, cost-effective and closed-tube microsatellite genotyping method well suited for molecular characterization of olive cultivars.